Developing Interactive Learning Media Based on Fowton - Dorahman, Boy; Nuraeni, Yeni; Rosnaningsih, Asih; Sunaryo, Sunaryo; Maulidyaputri, Rizka (International Journal for Educational and Vocational Studies, 2019)
This study was conducted to develop an interactive animation learning media in the fifth grade science learning of balanced nutritional food material in Pondok Pucung 01 Elementary School, South Tangerang. Data was collected through documentation techniques, interviews, questionnaires and validity. The analysis technique used is qualitative and quantitative analysis. Validation of this animated interactive learning media is guided by four aspects: 1) aspects of content and content, 2) aspects of display, 3) aspects of use and presentation, and 4) aspects of language. Validation by two media experts resulted in scores of 3.33 (very good) and 3.63 (very good). Validation carried out by two material experts in grade V SD produced scores of 3.66 (very good) and 3.36 (very good). Animated interactive learning media obtained a mean score of 3.49 from the score range 1-4 and included in the category "very good". This shows that the interactive interactive learning media developed are very suitable for use as elementary school science learning media.